Oncogenic role of rab escort protein 1 through EGFR and STAT3 pathway - Yun, Un-Jung (Cell Death Dis, 2017)
Rab escort protein-1 (REP1) is linked to choroideremia (CHM), an X-linked degenerative disorder caused by mutations of the gene encoding REP1 (CHM). REP1 mutant zebrafish showed excessive cell death throughout the body, including the eyes, indicating that REP1 is critical for cell survival, a hallmark of cancer. In the present study, we found that REP1 is overexpressed in human tumor tissues from cervical, lung, and colorectal cancer patients, whereas it is expressed at relatively low levels in the normal tissue counterparts. REP1 expression was also elevated in A549 lung cancer cells and HT-29 colon cancer cells compared with BEAS-2B normal lung and CCD-18Co normal colon epithelial cells, respectively. Interestingly, short interfering RNA (siRNA)-mediated REP1 knockdown-induced growth inhibition of cancer cell lines via downregulation of EGFR and inactivation of STAT3, but had a negligible effect on normal cell lines. Moreover, overexpression of REP1 in BEAS-2B cells enhanced cell growth and anchorage-independent colony formation with little increase in EGFR level and STAT3 activation. Furthermore, REP1 knockdown effectively reduced tumor growth in a mouse xenograft model via EGFR downregulation and STAT3 inactivation in vivo. These data suggest that REP1 plays an oncogenic role, driving tumorigenicity via EGFR and STAT3 signaling, and is a potential therapeutic target to control cancers.